The Medieval Sources of Anthropocentrism - Ganowicz-Bączyk, Anita (Studia Ecologiae et Bioethicae, 2011)
Anthropocentrism seems to be a key notion associated with the man-nature relation. Probably it is also the most controversial one in environmental ethics. The anthropocentric attitude is sometimes meant to be the main cause of the ecological crisis. One can distinguish at least several stages of the process, which led to this crisis, namely: stage of Magic and Myth, Ancient Times, Middle Ages, and Modern Times. The aim of this article is to show the process of development of an anthropocentric thought in Medieval European culture. Cultural changes of the Middle Ages, under the influence of Christianity among other things, led to the revaluation of the ancient way of thinking. The next step towards anthropocentric attitude in philosophy was made: the importance of the human individual increased, his needs and development became more vital than society as a whole. On the other hand, an essential aspect of medieval philosophy was rejecting the earthly world and turning to the transcendental one. One can distinguish three currents of medieval thought, which unlikely understood the meaning of the world and man as well as the way of cognition of reality. These are mysticism, rationalism, and empiricism. Mysticism negated both the value of nature and man as accidental entities. Nonetheless, it elevated man above other creatures. Rationalism assigned the man a central position in nature, for only human being among the accidental material entities is endowed with intellect and grace of faith., On the other hand, empiricism enhanced both nature (as the subject of cognition and exploitation) and man (as a rational being, who has some extraordinary abilities to use the environment to satisfy his needs). The process of drawing away from the holistic view on nature, of its desacralization and of tending towards controlling it started just in the Middle Ages. In the following ages antiteleologism developed in philosophy, which contributed to the growth of mechanism and rejecting the inherent value of nature in the Modern Times.